COMMUNITY PARTICIPATION IN PRESERVING THE MATTOJANG TRADITION IN Kamiri VILLAGE BALUSU DISTRICT, BARRU REGENCY - Andi Tenri Nippi; A.Pananrangi M (Meraja journal, 2021)
This study aims to provide a concrete description of how the participation of all elements of society in preserving the mattojang tradition in Kamiri Village, Balusu District, Barru Regency. In this research used descriptive qualitative research type. This research was conducted in Kamiri Village, Balusu District, Barru Regency which was carried out for 3 months starting from May-July 2021. Data collection techniques were: observation, interviews, and documentation. Then the data analysis technique used consists of three stages, namely; data reduction, data presentation, and drawing conclusions (Miles and Huberman 2014). The results of the study show that community participation in preserving the mattojang tradition in Kamiri village, Balusu district, Barru district from community leaders, traditional leaders, and perpetrators of the mattojang tradition can be categorized quite well. This conclusion is based on the results of data analysis through research indicators: mind participation, energy participation, mind participation and skill participation, goods participation and money participation. From the results of the study, it can also be concluded that community participation from the younger generation is categorized as quite low. Based on the data obtained, this condition is quite worrying considering that the number of parents who understand the mattojang tradition is decreasing. On the other hand, the number of young people is quite large, but their concern for the mattojang tradition is decreasing. Therefore, special attention is needed to make efforts to raise awareness of the younger generation so that they are more concerned with their traditions.